A field investigation of the thermal environment and adaptive thermal behavior in bedrooms in different climate regions in China. (17th December 2020) - Liu, Jinyu; Liu, Junjie; Lai, Dayi; Pei, Jingjing; Wei, Shen
Abstract: Sleep thermal environments substantially impact sleep quality. To study the sleep thermal environment and thermal comfort in China, this study carried out on‐site monitoring of thermal environmental parameters in peoples' homes, including 166 households in five climate zones, for one year. A questionnaire survey on sleep thermal comfort and adaptive behavior was also conducted. The results showed that the indoor temperature for sleep in northern China was more than 4°C higher than that in southern China in winter, while the indoor temperatures for sleep were similar in summer. Furthermore, 70% of people were satisfied with their sleep thermal environment. Due to the use of air conditioning and window opening in various areas in summer, people were satisfied with their sleep thermal environments. Due to the lack of central heating in the southern region in winter, people feel cold and their sleep thermal environment needs further improvement. The bedding insulation in summer and winter in northern China was 1.83clo and 2.67clo, respectively, and in southern China was 2.21clo and 3.17clo, respectively. Both northern China and southern China used air conditioning only in summer. People in southern China opened their windows all year, while those in northern China opened their windows during the summer and transitional periods.